2014
DOI: 10.1063/1.4896070
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Fe3O4–TiO2 core-shell nanoparticles

Abstract: Composite core-shell nanoparticles may have morpho-structural, magnetic, and optical (photoluminescence (PL)) properties different from each of the components considered separately. The properties of Fe3O4–TiO2 nanoparticles can be controlled by adjusting the titania amount (shell thinness). Core–shell nanoparticles were prepared by seed mediated growth of semiconductor (TiO2) through a modified sol-gel process onto preformed magnetite (Fe3O4) cores resulted from the co-precipitation method. The structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 56 publications
4
30
0
Order By: Relevance
“…In HRTEM images, the magnetic core is visible as a dark spot inside the bright spherical Schiff base complex grafted to O bond;Ti material. Our results agree with previous data presented in literature …”
Section: Resultssupporting
confidence: 94%
“…In HRTEM images, the magnetic core is visible as a dark spot inside the bright spherical Schiff base complex grafted to O bond;Ti material. Our results agree with previous data presented in literature …”
Section: Resultssupporting
confidence: 94%
“…The calculated optical band gap from (αhν) 1/2 versus hν plot for as-spun and annealed TNFs are 3.18 eV and 3.08 eV. The band gap of a semiconductor in generally decreases as the crystallite size increases [52]. Here it is clearly observed that the TNF band gap decreases due to the increase in crystallite size at higher annealing temperatures.…”
Section: Xrd and Raman Studiesmentioning
confidence: 71%
“…2b). In this process, the core/shell NPs is designed by growing a uniform shell on the core NPs through adsorption of the shell compound ions on the seed-mediated NPs [38, 39]. This growth technique can be used for the fabrication of NPs such as Fe 3 O 4 Au x Ag y with controlled size by acting on the precursor concentration of the shell component.…”
Section: Introductionmentioning
confidence: 99%